2014
DOI: 10.1371/journal.pone.0104819
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 28Si Ions, 56Fe Ions, and Protons on the Induction of Murine Acute Myeloid Leukemia and Hepatocellular Carcinoma

Abstract: Estimates of cancer risks posed to space-flight crews by exposure to high atomic number, high-energy (HZE) ions are subject to considerable uncertainty because epidemiological data do not exist for human populations exposed to similar radiation qualities. We assessed the carcinogenic effects of 300 MeV/n 28Si or 600 MeV/n 56Fe ions in a mouse model for radiation-induced acute myeloid leukemia and hepatocellular carcinoma. C3H/HeNCrl mice were irradiated with 0.1, 0.2, 0.4, or 1 Gy of 300 MeV/n 28Si ions, 600 M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
79
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(86 citation statements)
references
References 26 publications
6
79
0
Order By: Relevance
“…Further, translocations involving mouse chromosome 2 have been detected in a few cells from some cases of mouse rML [76,[78][79][80], in particular those induced by neutron exposure. Hence, the detection of cells with an abnormal chromosome 2 in some mice exposed to 300 MeV/n 28 Si ions may reflect the ability of 300 MeV/n 28 Si ions to induce ML [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, translocations involving mouse chromosome 2 have been detected in a few cells from some cases of mouse rML [76,[78][79][80], in particular those induced by neutron exposure. Hence, the detection of cells with an abnormal chromosome 2 in some mice exposed to 300 MeV/n 28 Si ions may reflect the ability of 300 MeV/n 28 Si ions to induce ML [12].…”
Section: Discussionmentioning
confidence: 99%
“…Such increases persisted up to 6 mos postirradiation, indicating (for the first time) the induction of chronic inflammatory responses in BM and heart tissues of mice exposed to 300 MeV/n 28 Si ions. Recently, it was found that 300 MeV/n 28 Si ions (in the dose range of 0.1-0.4 Gy) are capable of inducing ML in C3H/HeNCrl mice, a strain of mouse known to be susceptible to radiation-induced ML [12]. However, cellular/molecular mechanisms potentially occurring during 28 Si-ion-induced ML have not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Hepatocellular carcinoma in male C3H/HeNCrl mice (Weil et al, 2014) Dose response for Si and Fe particles was qualitatively different from γ -rays. Incidence of metastatic tumors significantly increased with Si and Fe particles compared to γ -rays or simulated solar protons.…”
Section: Tumor Modelmentioning
confidence: 92%
“…Several reports (Fry et al, 1985;Alpen et al, 1993;Dicello et al, 2004;Weil et al, 2009Weil et al, , 2014Grahn et al, 1992;Imaoka et al, 2007;Trani et al, 2010;Datta et al, 2013;Illa-Bochaca et al, 2014;Wang et al, 2015) have suggested that HZE particles and neutrons could produce more lethal tumors compared to tumors produced by low LET radiation or background tumors, which is a qualitative difference not accounted for in current risk estimates. Table 3 summarizes these findings from animal studies with HZE particle beams.…”
Section: Tumor Modelmentioning
confidence: 96%
“…Indirect information on HZE risk, obtained from radiation studies of rodents, has therefore been considered [e.g., (8)(9)(10)(11)(12)(13)]. One set of experiments, on murine Harderian gland (HG) tumorigenesis, has been influential in astronaut risk analysis [reviewed in ref.…”
Section: Background and Goalsmentioning
confidence: 99%